Let’s solve this equation step by step. You’re trying to get rid of the parentheses on the left by distributing the

2
1

to the 6x and to the 2. You can think of this as (
2
1

·6x)+(
2
1

·2).
2
1

(6x+2)
=
3x

+
=
3x

1 answer

Let's solve the equation step by step as you described. We're given the expression \( \frac{2}{1}(6x + 2) = 3x \).

Step 1: Distributing the \( \frac{2}{1} \) (which is just 2) to both terms inside the parentheses.

\[ 2(6x + 2) = 2 \cdot 6x + 2 \cdot 2 \]

Calculating each term:

  • \( 2 \cdot 6x = 12x \)
  • \( 2 \cdot 2 = 4 \)

So we can rewrite the equation as:

\[ 12x + 4 = 3x \]

Step 2: Rearranging the equation to isolate \( x \).

To isolate \( x \), we want to get all terms involving \( x \) on one side of the equation and the constant terms on the other side.

Subtract \( 3x \) from both sides:

\[ 12x + 4 - 3x = 3x - 3x \]

This simplifies to:

\[ 12x - 3x + 4 = 0 \]

Which further simplifies to:

\[ 9x + 4 = 0 \]

Step 3: Solving for \( x \).

Now, we need to isolate \( x \). First, subtract 4 from both sides:

\[ 9x = -4 \]

Now divide both sides by 9:

\[ x = -\frac{4}{9} \]

Solution:

The solution to the equation \( \frac{2}{1}(6x + 2) = 3x \) is

\[ x = -\frac{4}{9} \]